The Role of Cloud Computing and Artificial Intelligence Technologies on Cost Management in Smart Manufacturing: An Innovative Approach in Management Accounting - Rasha Jasim Ahmed Ebraheem Alobaidy (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This work investigated how artificial intelligence (AI) and cloud computing are related to cost control in smart manufacturing. It aims to show how these technologies improve manufacturing environments' decision-making and cost efficiency for better management accounting. The study thoroughly examined the literature for the qualitative research methodology. The cloud computing benefits from lowering operating costs, the use of AI in predictive maintenance, and the incorporation of these technologies into management accounting systems are only key area and trends from the thematic analysis. According to the results, offering scalable and flexible computing resources enabled companies to quickly adjust to shifting demands of the market, cloud computing greatly reduced costs. Yet, the study also emphasized the difficulties in the management of the resources, such as the possibility of inefficiencies and higher expenses due to inefficient resource distribution. Also, AI technologies enhance the efficiency and accuracy of accounting procedures, freeing up professionals for the concentration on strategic duties such as financial analysis and decision support. The report suggested that to reduce and avoid inefficiencies, businesses should carefully manage their cloud resources. For the improvement of operational efficiency and decision-making, businesses were required to include AI-driven solutions into their management accounting systems. The study also found that enterprises should give priority to implementing cloud computing and AI technologies to stay competitive in the quickly shifting smart manufacturing market. These technologies provide a substantial area for innovation in cost management.